Interaction of the Macrophage and Primitive Erythroid Lineages in the Mammalian Embryo - Palis, James (Frontiers in Immunology, 2017)
Two distinct forms of erythropoiesis, primitive and definitive, are found in mammals. Definitive erythroid precursors in the bone marrow mature in the physical context of macrophage cells in “erythroblastic islands”. In the murine embryo, overlapping waves of primitive and erythro-myeloid definitive (EMP) hematopoietic progenitors, each containing macrophage potential, arise in the yolk sac prior to the emergence of hematopoietic stem cells (HSC). Primitive erythroblasts mature in the bloodstream as a semi-synchronous cohort while macrophage cells derived from the yolk sac seed the fetal liver. Late-stage primitive erythroblasts associate with macrophage cells in erythroblastic islands in the fetal liver, indicating that primitive erythroblasts can interact with macrophage cells extravascularly. Like definitive erythroblasts, primitive erythroblasts physically associate with macrophages through α4 integrin-VCAM-1-mediated interactions and α4 integrin is redistributed onto the plasma membrane of primitive pyrenocytes. Both in vitro and in vivo studies indicate that fetal liver macrophage cells engulf primitive pyrenocytes. Taken together, these studies indicate that several aspects of the interplay between macrophage cells and maturing erythroid precursor cells are conserved during the ontogeny of mammalian organisms.